Impact of pneumococcal conjugate vaccine on invasive pneumococcal disease in children under 5 years of age in the Czech Republic - Kozakova, Jana; Krizova, Pavla; Maly, Marek (PloS one, 2021)
INTRODUCTION: The aim of this study is to analyse the impact of vaccination of infants with pneumococcal conjugate vaccine (PCV) on the incidence of invasive pneumococcal disease (IPD) in children under 5 years of age in the Czech Republic. MATERIAL AND METHODS: The present study includes all IPD cases reported in children aged 0-4 years within the surveillance program in 2007-2017. The impact of PCV is analysed for five categories of IPD: cases caused by all serotypes, cases caused by PCV7 serotypes (4, 6B, 9V, 14, 18C, 19F, and 23F), cases caused by three additional PCV10 serotypes (1, 5, and 7F), cases caused by three additional PCV13 serotypes (3, 6A, and 19A), and cases caused by non-PCV serotypes. To assess the impact of PCV, the study period was divided into the pre-vaccination period 2007-2008 and post-vaccination period 2009-2017, which was divided into three three-year parts: 2009-2011, 2012-2014, and 2015-2017. Analysis of differences between periods was based on the Poisson regression model where the population numbers were handled as an offset. RESULTS: The annual incidence of IPD in children under 5 years of age caused by all serotypes has had a downward trend since 2007: it dropped from 8.52/100 000 in 2007 to 2.67/100 000 in 2017, with slight increases in 2010 and 2013. All three post-vaccination periods show significantly lower (p<0.001) incidences in comparison to the pre-vaccination period, but they do not statistically significantly differ from each other. CONCLUSIONS: IPD surveillance data in the Czech Republic show that after the introduction of PCV vaccination of infants, there has been a significant decrease in the IPD incidence of children under 5 years of age. Continued IPD surveillance is essential to monitor for possible post-vaccination serotype replacement.
Keywords: séroskupina; Female; Infant; předškolní dítě; novorozenec; výsledek terapie; ženské pohlaví; DNA bakterií; vakcinace; Pneumococcal Vaccines; DNA, Bacterial; lidé; Infant, Newborn; Streptococcus pneumoniae; Treatment Outcome; kohortové studie; Incidence; Cohort Studies; Vaccination; Male; incidence; kojenec; pneumokokové vakcíny; ochrana veřejného zdraví; Czech Republic; Child, Preschool; Public Health Surveillance; Česká republika; mužské pohlaví; Vaccines, Conjugate; vakcíny konjugované; Pneumococcal Infections; pneumokokové infekce; Serogroup; Humans